2 Samuel 12 as retold by Josephus - Begg, Christopher (Verbum et ecclesia, 2006)
In this essay the author intends to focus on Josephus' retelling of the events of 2 Samuel 12. At the opening of his Antiquities, Josephus assures readers that in what follows he will not "add to" or "omit anything from" the Scripture records on which he is basing himself. Ant. 7.147-161, where on the one hand the basic content of 2 Samuel 12 is reproduced even in its details, while on the other additions, deletions, re-arrangements and other modifications of biblical data abound, offers an instructive example of how seriously, but also how flexibly, the historian carried through on that opening promise.